Germinação de sementes e desenvolvimento inicial de Erythrina mulungu (Mart. ex. Benth) - Conforto, Elenice de Cassia [UNESP]; Facincani, Adriana; Lima, Caroline Sprengel [UNESP]; Nanya, Lygia Harumi [UNESP]; Tralli, Marcela Palhiari [UNESP]; Lima, Náthali Maria Machado de [UNESP]; Nishimura, Renata Yumi Goulart [UNESP]; Andreoli, Regiane Peres [UNESP] (My University, 2014)
The aim of this study was to determine the best pre-germination treatments for seeds and the best size container for seedlings growing of coral tree Erythrina mulungu (Mart. ex. Benth). Among the treatments applied to seeds, scarification with sulfuric acid during 10 minutes and cutting stylus in the region opposite to hilum resulted, respectively, in highest values of germination percentage (82.8% and 82.1%) and rates of germination speed (1.15 and 1.71). The biometric variables indicated no effect of container size on leaf area and dry mass plants. At 63 days after sowing, although with Dickson quality score statistically similar (mean 0.26), only plants grown in small and large bags reached the diameter collect close to 5 mm, minimum recommended for field planting. According to the results, for initial development of coral tree, it is recommended pre-seed treatment with sulfuric acid commercial, sowing in plastic bags of 17 x 20 cm, and wait 63 days before planting in the field.

Objetivou-se escolher os melhores tratamentos pré-germinativos para as sementes e tamanhos de recipiente para o desenvolvimento inicial de plantas de Erythrina mulungu (Mart. ex. Benth). Dentre os tratamentos aplicados, a escarificação com ácido sulfúrico por 10 minutos e o corte com estilete na região oposta ao hilo resultaram, respectivamente, nos maiores resultados de porcentagem de germinação (82,8% e 82,1%) e índices de velocidade de germinação (1,15 e 1,71). Não foram observados efeitos do tamanho do recipiente sobre a área foliar e a produção de massa seca das plantas. Aos 63 dias após a semeadura, embora com índice de qualidade de Dickson estatisticamente similares (média de 0,26), somente as plantas cultivadas nos recipientes pequenos e grandes atingiram o diâmetro de coleto próximo de 5 mm, valor mínimo recomendado para o plantio em campo. Assim, para o desenvolvimento inicial desta espécie, recomenda-se o pré-tratamento das sementes com ácido sulfúrico comercial, semeadura em sacos plásticos para mudas de 17 x 20 cm, e aguardo de 63 dias até o plantio em campo.
Keywords: Fabaceae; diâmetro do coleto; escarificação; índice de qualidade de Dickson; Fabaceae; stem diameter; scarification; Dickson index of quality